A study on the position of workplace identity of employees - S. Faisal (International journal of human capital in urban management (Online), 2024)
BACKGROUND AND OBJECTIVES: Multiple organizational concepts are paramount in the workplace. Workplace Identity is one among them. It is a multidimensional concept that explores one's self-concept and understanding of their occupational roles. It is a concept of immense significance that directly impacts various organizational behavior aspects, such as job involvement, employee commitment, workplace learning, and stress management. The concept is indispensable for any individual as it helps tide over the pervasive uncertainties and tribulations in any organization. The Saudi economy is in a deep transition phase. It is all set to leap forward in terms of quality and quantity. Against this backdrop, if it is to face the multiple inherent challenges successfully, it requires a healthy band of the working class who are aware of and have a relatively high level of workplace identity. However, a fair review of the literature shows that scant evidence exists about the position of Workplace identity among the Saudi working class. The proposed study intends to fill this gap in the literature. The study intends to identify the level of the important concept of Workplace identity among the Saudi workforce- both male and female. It also intends to examine the relationship with human capital.METHODS: A quantitative research design was employed for the study. Data for the study was collected randomly from Saudi Arabia and India. 210 samples were from Saudi Arabia, and 248 were from India. Regression was employed to analyze the collected data using SPSS (version 22.0).FINDINGS: The study found that human capital contributes to workplace identity as the value of the F statistic was 15.978 which is significant. In addition, the results show that females have a higher workplace identity. The results also indicate significant differences (0.01 level) between the Indian and Saudi samples in all the factors and the overall workplace identity.CONCLUSION: The study provides inputs toward future directions in making the Saudi workforce competitive and dynamic. The study's findings, which are useful for academics and practitioners, are also expected to trigger further studies in this hitherto unexplored area of organizational behavior.